Integration Strategy of Green City Development With the Indragiri Rokan River Flow Area in the Capital Area of Solok Regency “Arosuka” - Gusmal Gusmal; Agus Irianto (Journal Research of Social Science, Economics, and Management, 2022)
This study formulates a green city development strategy in the capital city of Solok Regency in the "Arosuka" area. The strategy in question is an integration strategy where this area has its own uniqueness because it is located in the Indragiri Rokan Catchment Area. The development of an environmentally friendly city is usually associated with waste management, slum settlements, architecture, sustainable development and other issues, but this article focuses on efforts to maintain groundwater discharge in Arosuka in connection with the change in the status of the Catchment Area area to become the capital of an integrated shark Catchment Area city. The data used is secondary data in the form of a regency capital   development plan, Catchment Area and Arosuka area data. The research method uses a descriptive qualitative approach. The results of the study indicate that there are 5 strategies for structuring the Arosuka area so that it is expected to become a green city in the Indragiri Rokan Catchment Area.